Evidence from paranoid schizophrenia for more than one component of theory of mind - Scherzer, Peter; Achim, André; Léveillé, Edith; Boisseau, Emilie; Stip, Emmanuel (Frontiers in Psychology, 2015)
We previously reported finding that performance was impaired on four out of five theory of mind (ToM) tests in a group of 21 individuals diagnosed with paranoid schizophrenia (pScz), relative to a non-clinical group of 29 individuals (Scherzer, Léveillé, Achim, Scherzer, Boisseau, & Stip, 2012). Only the Reading the Mind in the Eyes Test (RMET) did not distinguish between groups. A principal components analysis revealed that the results on the ToM battery could be explained by one general ToM factor with the possibility of a latent second factor. As well, the tests were not equally sensitive to the pathology. There was also overmentalization in some ToM tests and under-mentalisation in others. These results led us to postulate that there is more than one component to ToM. We hypothesized that correlations between the different EF measures and ToM tests would differ sufficiently within and between groups to support this hypothesis. We considered the relationship between the performance on eight EF tests and five ToM tests in the same diagnosed and non-clinical individuals as in the first study. The ToM test shared few EF correlates and each had its own best EF predictor.. These findings support the hypothesis of multiple ToM components